Understanding the Differential Roles of Major Causal Factors in the 2017 Delhi Smog through an Analysis of Satellite, Meteorological and Pollution Data - Awadhiya, Ankur (Indian Forester, 2019)
The paper describes an analysis of publicly available satellite, meteorological and pollution data to investigate the differential roles of major causal factors in the 2017 Delhi smog. The investigation revealed that the prevailing weather conditions and the burning of crackers on Diwali and agricultural (paddy) residues on fields may have had significant roles in creating and continuing the smog, when compared to other factors such as automobiles and industries which are mainly responsible for worsening the smog situation. Suggestions for the present and future management of smogs are also provided.